शास्त्रवर्याः - (:unkn) unknown (Kavikulguru Kalidas Sanskrit Vishwavidyalaya Ramtek Nagpur Maharashtra, 2004)
Shastravaryah is a Sanskrit literature book for children. The book deals with biographies of prominent and renowned personalities.
Shastravaryah
Keywords: शास्त्रवर्याः; Shastravaryah; Children's literature; Sanskrit